P-231 YI Patient Experience Living with Inflammatory Bowel Disease. (March 2016) - Chauhan, Usha; Popov, Jelena; Marshall, John; Armstrong, David; Halder, Smita; Tse, Frances; Wickson-Griffiths, Abigail; Kaasalainen, Sharon; Farbod, Yasamin; Moayyedi, Paul
Abstract : Background: Inflammatory bowel disease (IBD) is a lifelong chronic inflammation of the digestive tract which often presents early in life. The 2 main IBD phenotypes are Crohn's disease (CD) and ulcerative Colitis (UC). The chronic relapsing nature of the disease results in lasting physical, psychological and social stress. As part of a larger study, the primary objective of this study was to examine patients' experiences and to determine challenges associated with living with IBD. Methods: Using a qualitative descriptive approach, data was collected using 5 focus group sessions with a total of 17 individuals with diagnosis of IBD. The focus group sessions were audiotaped, transcribed, coded and analyzed using thematic content analysis. Results: Seventeen IBD patients with average age of 44, ranged from 25 to 77, (15 CD, 2 UC, 8F, 9M), with average disease duration of 19 years were included. The main theme across the 5 focus groups was: "IBD controls your life." This was further divided into 4 sub-themes: (1) long duration from onset of symptoms to diagnosis; (2) poor experience with initial treatment; (3) lack of public knowledge of IBD requiring self-advocacy; (4) managing the psychosocial, emotional and financial impact of disease. Discussing with patients their issues with living with IBD, there were similar experiences and challenges, including lack of understanding from school and work force were reported. Initial symptoms were dismissed as attention seeking behavior, in those diagnosed during teen years. Following diagnosis, patients' main concern was choosing the right career path while effectively managing their IBD. However, advanced prearrangement of special accommodation for schoolwork, and time off from school and work for follow-up appointments continued to be a source of difficulty. Inability to hold a fulltime employment, early retirement and out of pocket expenses not covered by various funding agencies lead to financial struggles. Psychosocial impacts were often associated with the inability to travel and attend social events due to IBD-induced constraints, such as fear of pain and fear of incontinence. This often led to feelings of isolation, exclusion, and deep depression. The duration of disease of our patients' allowed them to provide useful insights into the effectiveness of modern treatments in comparison to traditional approaches. The overwhelming consensus was that current biological treatments are significantly more effective and tolerable than the use of corticosteroids and surgical intervention, which were felt by some patients, to have caused additional health problems. Conclusions: Despite the demographic differences in our sample size, several themes were found to be common among the 5 focus groups. The general consensus in terms of the greatest difficulties associated with living with IBD was garnering understanding from others and learning to live their lives around the disease. However, the main, unifying theme that emerged from the findings was that IBD plays a significant role in many different facets of the lives of the patients, and learning to manage and cope with the burden of symptoms and its effects on daily life becomes a lifelong process.